Bochdalek hernia causing ureteric obstruction a rare association: about one case report - llyass Laaribi; Ikram Zaid; Samia Berrichi; Houssam Bkiyar (Urology Case Reports)
Bochdalek hernias, is rare form of hernia, typically manifesting in neonates. Adult occurrences are unusual and often asymptomatic discovered accidently. Visceral involvement may include stomach, colon, spleen, or kidney, but diaphragmatic herniation of the ureter is exceptionally uncommon, with only a handful of cases published. Timely detection is essential, to avoid irreversible damage, We present a case of a 82-year-old man who presented right Bochdalek hernia involving the right ureter, causing ureterohydronephrosis.